Peran Pondok Persulukan Babussalam Baru Sei Titi An-Nur dalam Membangun Akhlakul Karimah Masyarakat Desa Huta Baru Kecamatan Simangambat Padang Lawas Utara - Harahap, Jainuddin (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2024)
Based on the results of interviews and analysis of the role of the New Babussalam Sei Titi An-Nur Sulukan Lodge in building the Akhlakul Karimah community in Huta Baru Village, it can be concluded that the religious practice of Sufism in the formation of Akhlakul Karimah in the New Babussalam Sei Titi An-Nur Sulukan Hut in Huta Baru Village. According to the results of an interview conducted by the author with the head of Pondok Persulakan Babussalam Baru Sei Titi An-Nur, Huta Baru village, Khalifa Makmur Siregar said that "For pilgrims or people who practice suluk teachings which are the same as tariqa science, they must carry out their malai by adhering to the Quran and also Hadith. The practice of suluk knowledge must understand the rules contained in it so that it is equal to ma'rifat. In its silver, pilgrims must carry out practices that are in accordance with the teachings of the tariqat at the new Babussalam Sei Titi An-Nur hut in Huta Baru Village including, dhikr, berakhlakul karimah (morals to Allah Almighty, morals to humans, akhalak to themselves and morals to murshid or teachers), and instill the nature of muqarbah. that way man will always be consistent in worship, because he is always supervised and does not escape his supervision. The practice of tariqat taught by the new babussalam Islamic boarding school sei titi an-nur huta baru village. Although there are some variations, excavations from several sources reveal at least four series of rituals carried out in the tariqa including: First, Baiat, is a process of saying the pledge of allegiance to practice all the knowledge and teachings of the tariqa given. Second, tawajjuh "sitting face to face", an assessment process carried out by spiritual guides to determine the level of readiness and ability of students to accept the transformation of religious science. Third, dhikr / nafus / suluk, although there are slight differences, but these three rituals contain the practice of a series of spiritual rituals for the purpose of purifying the heart before receiving knowledge transfer from the spiritual guide. Fourth, khataman, completes the entire series of rituals at all levels from the lowest level to the highest with the opinion of full assistance from the spiritual guide.  The method used by the leader of the Babussalam Baru Sei Titi An-Nur hut in Huta Baru Village, uses habituation and advice methods. It is run every Tuesday after tawajjuhan. Using habituation methods that are carried out repeatedly so that something can become a habit. To achieve perfect morals also includes the purpose of the tariqa in this tariqa council which emphasizes the character of karimah and how to apply it in daily life. The method of advice by giving advice is subtle, gentle, and considerate. On the other hand, in this moral builder, it can also be seen from the routine of remembrance, tawajjuhan, suluk which always remembers Allah SWT. and makes the heart calmer and has the morals of karimah, uswatun hasanah, and also rahmatal lil alamin.